Fuzzy-controlled battery charger state-of-charge controller - Rahim, N.A.; Mekhilef, Saad; Chan, E.L.; Ping, H.W. (2006)
This paper presents a fuzzy-controlled state-of-charge controller for battery charger application. The proposed battery charger is constructed based on a boost-buck converter and equipped with a fuzzy logic controller to improve the efficiency of charging process and to deliver maximum output power to the battery. A digital signal processor (DSP)-based system is designed to implement the pulse width modulation (PWM) waveforms generator and to perform fuzzy control feedback algorithm. The PWM generator supplies gating signals for the converters, and the fuzzy controller provides control over the PWM pattern. The fuzzy controller continuously monitors the state-of-charge of the battery, after which the fuzzy inference determines the duty cycle of the PWM to change the charging current accordingly.